Characeristics of sediments in Tri An hydropower lake - Thuận, Đinh Văn; Hà, Vũ Văn; Tân, Mai Thành; Tấn, Nguyễn Trọng; Lương, Lê Đức; Tạo, Nguyễn Văn; Hà, Trịnh Thị Thanh (Vietnam Journal of Earth Sciences, 2014)
Studying the sediment characteristics of Tri An lake is based on the analysis of 96 grain-size, 39 clay mineral and 42 Pb-Ra samples taken from 42 positions in the lake. The mean diameter (Md) decreases from upstream to downstream of the Tri An lake. The poor sorting (So) with values over 2 in all samples mean that their sedimentary environment is strong variation. The analysis show that, Chlorite and Quartz contents in center are higher than near shore of lake, meanwhile Kaolin and Gibbsite are in contrary. Sedimentation in the lake differ from one place to another. The upstream is marked highest rate with value from 2.0 to 5.24cm/year; the center has moderate value; the downstream and near-shore area reach the lowest rate from 0 to 0.5cm /year